2012
DOI: 10.1002/cne.23085
|View full text |Cite
|
Sign up to set email alerts
|

A novel phenotype for the dynein heavy chain mutation Loa: Altered dendritic morphology, organelle density, and reduced numbers of trigeminal motoneurons

Abstract: Dynein, the retrograde motor protein, is essential for the transport of cargo along axons and proximal dendrites in neurons. The dynein heavy chain mutation, Loa, has been reported to cause degeneration of spinal motor neurons, as well as defects of spinal sensory proprioceptive neurons, but cranial nerve nuclei have received little attention. Here, we examined the number and morphology of neurons in cranial nerve nuclei of young, adult and aged heterozygous Loa mice, with focus on the trigeminal, facial, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 71 publications
(134 reference statements)
1
10
0
Order By: Relevance
“…It would thus be of interest to test if KIF1A and KIF1Bβ mediate lysosome transport in dendrites. Alternatively, lysosome transport in dendrites could be mediated by dynein, as shown in previous studies (20,33,70). Further studies will be needed to assess the relative contributions of different microtubule motors to lysosome transport in dendrites.…”
Section: Requirement Of Borc-dependent Lysosome Transport For Autophamentioning
confidence: 77%
“…It would thus be of interest to test if KIF1A and KIF1Bβ mediate lysosome transport in dendrites. Alternatively, lysosome transport in dendrites could be mediated by dynein, as shown in previous studies (20,33,70). Further studies will be needed to assess the relative contributions of different microtubule motors to lysosome transport in dendrites.…”
Section: Requirement Of Borc-dependent Lysosome Transport For Autophamentioning
confidence: 77%
“…The phenotype of the Loa/+ mouse differs considerably between the cranial and the spinal levels of the neuraxis. -motoneuron loss in the trigeminal motor nucleus was already apparent at an early postnatal age and progressed only minimally with age [37]. These findings give rise to questions of how dynein dysfunction results in selective neural degeneration, especially selective motor neuron degeneration.…”
Section: Charcot-marie-tooth (Cmt) Diseasementioning
confidence: 97%
“…While our study suggested that Loa/+ mice also suffered from early-onset proprioceptive sensory neuropathy or possibly primary effects on the sensory neurons. A recent study by Wiggins [37], found that Loa/+ mice displayed deficits in both the motor and sensory nervous system. This argues against a model primarily involving sensory loss.…”
Section: Charcot-marie-tooth (Cmt) Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The heterozygous Loa/+ mice develop pathological features similar to the SMA-LED early onset: abnormal motor neuron innervation, decreased number of spinal cord ventral horn motor neurons, motor neuron degeneration, impaired coordination, abnormal grip strength, muscle spasms, accumulation of fat in tissues and abnormal mitochondrial morphology and function [7-10]. Typical pathological findings in heterozygous Loa/+ mice include early-onset degeneration of spinal motor neurons and proprioceptive sensory neuropathy, muscle spindle deficiency, neuromuscular junction defects, neuronal migration, alteration of axonal transport of cargoes, abnormalities due to alteration of the morphology of motor neurons and vacuolar mitochondria [8, 11-13]. It was proposed that such changes in morphology of mitochondria correlate with oxidative stress in other neurodegenerative diseases with imbalance between oxidant and antioxidant proteins [14-16].…”
Section: Introductionmentioning
confidence: 99%